2011
DOI: 10.1002/ceat.201000535
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behavior of Organic Dyes in Biopolymers Impregnated with H3PO4: Thermodynamic and Equilibrium Studies

Abstract: A lignocellulose-based waste biopolymer was impregnated with phosphoric acid and used for the removal of two organic dyes, Direct Blue (DB) and Reactive Blue (RB), from aqueous solution. Batch adsorption kinetic studies were carried out at different initial concentrations of the dyes, at different temperatures and various initial pH values (2-10). The equilibrium data obeyed the Langmuir isotherm model with high regression coefficient. The kinetic data were also used to test three different kinetic models. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…This indicates that activated adsorption may occur between the dye molecule and the functional groups of organic components such as cellulose and lignin on CS, CW, and CD. Similar results have also been reported for the adsorption kinetics of acid orange 10 onto organobentonite, 7 for the adsorption kinetics of direct blue and reactive blue onto lingnocellulose-based waste biopolymer, 8 and for the kinetics of MB adsorption onto perlite 12 and banana stalk waste. 25 On the other hand, if the correlation coefficients estimated from the plots of the intraparticle diffusion kinetics are more than 0.90, the regression may be regarded as linear.…”
Section: The Pseudo-second-order Kinetics Of Mb Adsorption On Cs Cw and CD For Different Temperaturessupporting
confidence: 84%
See 1 more Smart Citation
“…This indicates that activated adsorption may occur between the dye molecule and the functional groups of organic components such as cellulose and lignin on CS, CW, and CD. Similar results have also been reported for the adsorption kinetics of acid orange 10 onto organobentonite, 7 for the adsorption kinetics of direct blue and reactive blue onto lingnocellulose-based waste biopolymer, 8 and for the kinetics of MB adsorption onto perlite 12 and banana stalk waste. 25 On the other hand, if the correlation coefficients estimated from the plots of the intraparticle diffusion kinetics are more than 0.90, the regression may be regarded as linear.…”
Section: The Pseudo-second-order Kinetics Of Mb Adsorption On Cs Cw and CD For Different Temperaturessupporting
confidence: 84%
“…7 Senthilkumaar et al have investigated the adsorption kinetics of direct blue and reactive blue by a lignocellulose-based waste * Correspondence: acemioglu@kilis.edu.tr biopolymer. 8 Hameed and El-Khaiary have studied the adsorption kinetics of methylene blue (MB) using broad bean peels. 9 Yao et al have investigated the adsorption kinetics of MB by Xanthoceras sorbifolia seed coat (XSSC), a bioenergy forest waste.…”
Section: Introductionmentioning
confidence: 99%
“…This revealed that the adsorbent's large surface area and many adsorption sites contributed to an increase in the percentage dye adsorbed; hence, a little increase in the amount of adsorbent provided a signi cantly greater surface area to absorb huge numbers of MB molecules. In the literature, 24 the same outcome has been described.…”
Section: Resultssupporting
confidence: 53%
“…Adsorption is reduced due to the lack of sufficient available open sites to adsorb high initial concentrations of the dye [ 11 , 12 , 13 , 14 , 15 , 16 ]. This situation is caused by the mass transfer driving force, which increases when the initial concentration is increased, resulting in higher adsorption of dyes [ 42 , 43 ]. Various studies have confirmed that adsorption capacity increases as the dye concentration increases [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%